STARs in the CNS. (15th August 2016) - Ehrmann, Ingrid; Fort, Philippe; Elliott, David J.
Abstract : STAR (signal transduction and activation of RNA) proteins regulate splicing of target genes that have roles in neural connectivity, survival and myelination in the vertebrate nervous system. These regulated splicing targets include mRNAs such as the Neurexins (Nrxn), SMN2 (survival of motor neuron) and MAG (myelin-associated glycoprotein). Recent work has made it possible to identify and validate STAR protein splicing targets in vivo by using genetically modified mouse models. In this review, we will discuss the importance of STAR protein splicing targets in the CNS (central nervous system).